Antibacterial Activity of -guaiene Patchouli Oil on Staphylococcus aureus and Staphylococcus epidermidis - Novia Dwi Anggraeni; Sarifah Nurjanah; Elazmanawati Lembong (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Patchouli oil has the content of α-guaiene as one of the dominant components. The α-guaiene compound is one of the seskuiterpen groups that has antibacterial capabilities, but there have been no reports of antimicrobial activity of the α-guaiene compound. Staphylococcus aureus and Staphylococcus epidermidis bacteria are normal human microbials that often cause nosocomial infections (originating from hospital environments). This study aims to find out the antibacterial activity of α-guaiene with a purity of 37,50%. The method used is the test of the diameter of the well diffusion method against the bacteria S. aureus ATCC 25923 and S. epidermidis ATCC 12228. The study used variations in α-guaiene concentrations of 20%, 40%, 60%, 80%, and 100%. The α-guaiene material used is the result of the process of distillation fractionation of patchouli oil, so that it is obtained α-guaiene components with a purity of 37,50%. The results showed that the α-guaiene components with purity of 37,50% able to inhibit the growth of both test bacteria, with the highest antibacterial activity found in the bacteria S. aureus in concentration variation of 60% with an average resistance diameter value of 10,33 mm. In conclusion, α-guaiene components with purity of 37,50% indicate the existence of antibacterial activity.